Adherence to surveillance guidelines in resected NSCLC: Physician compliance and impact on outcomes. (October 2017) - Ho, Cheryl; Siegfried, Jennifer; Remo, Karen; Laskin, Janessa
Highlights: Guidelines generally recommend follow up every 6 months for resected NSCLC. Compliance with clinic visits and/or CT scans was 80% in our study. Curative intent therapy was not higher in the group followed guidelines. Palliative chemotherapy trended towards higher use in patients followed guidelines. Routine post-op surveillance did not appear to improve clinically relevant outcomes. Abstract: Background: Resected NSCLC guidelines have varying recommendations on appropriate post-operative surveillance. There is general consensus that patients require follow-up with clinic visits and/or CT scans every 6 months for the first 2 years. This study evaluated compliance with surveillance guidelines and the impact on outcomes. Methods: The BC Cancer Agency (BCCA) provides cancer control for 4.6 million individuals. Inclusion criteria included referred patients from 2005 to 2010, resected stage Ib/II NSCLC, minimum 2 years follow-up at the BCCA, no prior cancer within 5 years. Retrospective chart review collected baseline parameters, follow up visits, CT imaging, recurrence and death. Results: 479 were referred and 263 were eligible. Baseline characteristics: median age 68, male 52%, current/former/never smoker 38/52/10%, stage Ib/II 51/49%, squamous/non 30%/70%. Adherence to visits and/or CT scans every 6 months in 2 years: clinic visits 77%, CT scans 35%, visit and/or CT 80%. Recurrence rate was 46% at 2 years. Surveillance below vs per/above guidelines; metastatic recurrence 57% vs 79% (p = 0.28), curative intent treatment at recurrence 14% vs 9% (p = 0.50), palliative systemic treatment given 14% vs 34% (p = 0.42), DFS 66.6 m vs 37.6 m (p < 0.001), OS 76.5 m vs 37.7 m (p < 0.001). Conclusions: Compliance with follow up recommendations for resected NSCLC was 80%. Guideline conformity did not increase the rate of curative treatment at recurrence nor did it increase the proportion of patients treated with palliative chemotherapy. Better adjuvant treatment and surveillance options are needed for resected NSCLC.